Add-on effects of oral tocopherol supplementation to surgical varicocelectomy on the outcome of assisted reproductive technology: a single-center pilot study report - Takeshima, Teppei; Mihara, Takahiro; Tomita, Makoto; Kuroda, Shinnosuke; Yumura, Yasushi; Ueno, Hiroe; Yamamoto, Mizuki; Murase, Mariko (Frontiers in Reproductive Health, 2024)
Introduction Varicocelectomy is well known to improve the pregnancy outcome of patients with clinical varicoceles in assisted reproductive technologies as well as spontaneous conception. Therefore, this study aimed to evaluate the additional effects of oral antioxidant therapy after varicocelectomy on the pregnancy outcome in the assisted reproductive technology setting. Methods This study was a retrospective cohort study. The subjects were couples among whom the male partner had undergone varicocelectomy and was scheduled for subsequent assisted reproductive technology. Pregnancy outcomes were followed retrospectively in 62 couples with male partners who received tocopherol (antioxidant group) and 37 couples who did not (control group). The tocopherol and control groups were assigned dependent on the decision of the physician in charge and the patient's request. The clinical pregnancy rates per couple and embryo transfer, time to pregnancy, and the number of cycles during transfer to pregnancy were evaluated. Results No significant differences were observed in the pregnancy rate per couple (antioxidant group 70.9% vs. control group 64.9%, P = 0.55) and per embryo transfer (50.4% vs. 39.6%, P = 0.22). Regarding the time to event analyzed by adjusted restricted mean survival time, the mean time to pregnancy was significantly shorter in the antioxidant (tocopherol) group (14.2 vs. 17.4 months, P = 0.025). No significant difference was observed in the embryo transfer cycle to pregnancy (mean embryo transfer cycles: 2.6 vs. 3.0, P = 0.238). Conclusions Additional oral tocopherol nicotinate as antioxidant therapy after varicocelectomy was shown to shorten the time to pregnancy. It is recommended that add-on effects be tested in more well-designed randomized controlled trials to examine whether it improves assisted reproductive outcomes.